Environmental and individual correlates of distress: Testing Karasek's Demand‐Control model in 99 primary care clinical environments. (15th October 2013) - Presseau, Justin; Johnston, Marie; Johnston, Derek W.; Elovainio, Marko; Hrisos, Susan; Steen, Nick; Stamp, Elaine; Francis, Jill J.; Grimshaw, Jeremy M.; Hawthorne, Gillian; Hunter, Margaret; Eccles, Martin P.
<x xml:space="preserve">Abstract</x> Objectives Karasek's job demand‐control model postulates that demand, control, and distress are environmental rather than individual features although these levels are often confounded. The objective was to investigate whether job demand, control, and demand × control predict environmental and individual distress in primary care clinicians, and the mediating role of distress in the relationships between demand and control with intention to leave and absenteeism. Design Predictive national survey. Methods We invited 2, 079 staff from 99 general practices in the United Kingdom (843 GPs and nurses, 1, 236 administrators) to complete postal questionnaires assessing distress, intention to leave, absenteeism, job demand, and control. Random intercept multilevel models and bootstrapped mediation models were run to test the study hypotheses. Results One thousand five hundred and ninety staff completed questionnaires (77% staff‐level response rate; complete responses by ≥80% of all workers in 68 work environments). There was evidence of environmental variation between practices in intention to leave, absenteeism, job demand, and control, but not distress. Job demand and control both significantly predicted distress, and control moderated the relationship between demand and distress with the effects of demand being reduced at low levels by high control. A small indirect effect via distress was observed for the relationship between job demand and absenteeism, and between job control and intention to leave. No support was found for environmental effects of work settings on distress, but there was evidence of individual‐level effects. Conclusions There is a need for considering environmental and individual levels and a danger of generalizing conclusions from one level to the other. Statement of contribution What is already known on this subject? Karasek's job demand‐control model shows consistent prediction of distress in health professionals. Environmental and individual features of distress, demand, and control are often confounded. What does this study add? Nationally representative UK survey of doctors, nurses, and admin primary care staff. Test individual and environment effect of demand and control on distress, absenteeism, leaving intention. Indirect effect of demand on absenteeism via distress and of control on intention to leave via distress.